Metaphorical somatonyms of northern Samogitians: artefactual motivational model - Lubienė, Jūratė; Pakalniškienė, Dalia (Lietuvių kalba, 2020)
The article presents the analysis of the onomasiological structure of the metaphorical somatonyms of Northern Samogitians, focusing on the indicators of the source of metaphors. Based on the explicit semantics of the source (lexical motivators), the metaphorical somatonyms of Northern Samogitians belong to several motivational models, the most productive of which is the artefactual motivational model. The basis of the artefactual metaphor is the associative similarity of the object (artefact) and the body part according to various parameters – shape, size, features of structure and materiality, actions, especially repetitive movements.